Exudative pleural effusion caused by lung fluke infection: case report. (January 2022) - Ai, Ling; Li, Jingyuan; Ye, Ting; Wang, Wenjun; Li, Yuying
Highlights: Lung fluke infection is a rare cause of exudative pleural effusion. Infected patients may have eosinophilia and special dietary habits. Pleural biopsy helps to distinguish other aetiologies. Positive serological tests can confirm infection. ABSTRACT: The global incidence of lung fluke disease is low, and the infection is a rare cause of pleural effusion in adults. This article reports a case of exudative pleural effusion accompanied by eosinophilia in a 19-year-old male which was finally proven to be caused by lung fluke infection through antibody testing. This case highlights that lung fluke infection is an easily overlooked cause of pleural effusion. Eosinophilia is a potential marker of infection, and serological tests could further confirm the diagnosis.